1995
DOI: 10.4148/2378-5977.2024
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur amino acid utilization by growing steers (1995)

Abstract: SummaryTwo studies were conducted to evaluate sulfur amino acid requirements of growing steers. In trial 1, six ruminally cannulated steers (352 lb) were used to determine methionine requirements . Treatments were abomasal infusi ons of 0, 2, 4, 6, 8, or 10 g/day of Lmethion ine. Steers were fed 5.8 lb of a soyhull and wheat straw based diet. Continuous infusion s of acetate, propionate, and butyrate into the rumen and of dextrose into the abomasum were made to increase energy. Amino acids other than methionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
60
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(74 citation statements)
references
References 0 publications
13
60
0
1
Order By: Relevance
“…Considering that Met represents roughly 2% of the body protein (Gabel et al, 1988), the efficacy of deposition of the infused Met reached 12.5% in this study, whereas values obtained by Campbell et al (1997) and Titgemeyer et Merchen (1990a) were, respectively, 24 and 33%. These values confirm that Met is probably used to ends other than protein accretion.…”
Section: Methodsmentioning
confidence: 80%
See 4 more Smart Citations
“…Considering that Met represents roughly 2% of the body protein (Gabel et al, 1988), the efficacy of deposition of the infused Met reached 12.5% in this study, whereas values obtained by Campbell et al (1997) and Titgemeyer et Merchen (1990a) were, respectively, 24 and 33%. These values confirm that Met is probably used to ends other than protein accretion.…”
Section: Methodsmentioning
confidence: 80%
“…Campbell et al (1997) reported, however, that Met requirement was near 8.4 g/d when the Cys supply reached 2.1 g/d and that supplementation of Cys did not spare Met. The proportion of Met and Cys provided in this study is, therefore, very close to that of Campbell et al (1997).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations